High-temperature centrifugal separation of Cu from waste printed circuit boards. (20th October 2018) - Meng, Long; Zhong, Yiwei; Guo, Lei; Wang, Zhe; Chen, Kuiyuan; Guo, Zhancheng
Abstract: Supergravity separation by high-temperature centrifugation is an effective and environmentally friendly method for separating and recycling comminuted waste printed circuit boards (WPCBs). Present work is focused on the recovery of Cu from WPCBs by supergravity separation at high temperature. A two-step separation process was adopted to selectively recover Cu alloys at different temperatures. The results indicated that temperature has a significant influence on the composition of the resultant SnCu alloy, while the gravity coefficient, which may be adjusted by varying the centrifugation speed, has little effect on alloy composition and only affects the Cu recovery rate in the separation of the SnCu alloy. Following separation, the Cu contents of the alloys were more than 85 wt%. Under optimized conditions, i.e., a temperature of 1300 °C, a gravity coefficient of 1000, and a separation time of 5 min, the total recovery values achieved for Cu, Zn, Pb, and Sn were 93.56%, 65.07%, 92.92%, and 95.52%, respectively, for the whole separation process. This process provides a clean and efficient method for reclaiming valuable metals from WPCBs and preventing environmental pollution. Highlights: Centrifugation mediated supergravity separation was used to recover Cu from PCBs. At optimized conditions, recovery levels of Cu, Pb, and Sn were higher than 92%. This process offers a new way of recovering for recycling valuable metals from PCBs. A large-scale experimental apparatus was designed for handling large volume of PCBs.